PENYULUHAN PENCEGAHAN STUNTING DENGAN MEDIA SENAM DI DESA SADANG, KECAMATAN JEKULO, KUDUS - Kharisma Aprilita Rosyidah; Hasriyani Hasriyani; Dewi Hartinah; Atun Wigati; Khamid Khanafi (Universitas Muhammadiyah Kudus, 2023)
According to data released by UNICEF, the highest number of cases of stunting is in Africa and Asia, including Indonesia. Riskesdas Indonesia data shows that more than a third (30.8%) of the toddler population experiences stunting, which must be addressed immediately. This community service activity aims to increase the knowledge of the people of Desa Sadang, Kecamatan Jekulo, Kabupaten Kudus, where the activities carried out include several stages, namely the delivery of material related to what stunting is and its prevalence in Central Java, the characteristics of stunted toddlers and efforts that can be taken. community to prevent stunting, question and answer and evaluation of material with a post-test, joint exercise led by students to form the